Estudo das reações transfusionais agudas em um hospital escola de Goiânia-GO - Valério, Vivianne Teixeira Duarte (2015)
Blood transfusion is a well-established and an essential therapy in clinical settings. In practical terms, blood transfusion presents risks to the receptor even when it is properly administered and when it follows transfusion rules; This adverse events may occur, they so-called transfusion reaction. The present study evaluate acute transfusion reaction in the Clinical Hospital of Goiás between January to June 2014. This is a prospective epidemiological study based on a quantitative approach. We performed data collection through two different ways. Firstly by an active search for evidence of acute transfusion reaction in transfusion and medical records and secondly by spontaneous reporting. Data collection started after the Research Ethics Committee approval report number 490,699. After the data collection, they were recorded and analyzed using the statistical software Bioestat 5.0. We adopted a significance level of 5% (p ≤ 0.05) or all the analyzes. The rate of acute transfusion reactions analyzed by active search was 10.6 in 852 transfusions and 1.8 of spontaneous reports in 5440 transfusions, covering an underreporting rate of 47.4%. The packed red blood cells prevailed as the most common blood component in transfusion related to reactions (61.3%). Age and gender distribution were not statistically significant (p = 0.0912 and 0.9982 respectively). Allergic reaction was the most common event (n = 13, 68.4%). Interestingly the rate of febrile non-hemolytic transfusion reaction was small (n=2, 10.5%), the volume overload represented (n=2, 10.5%) of the reactions and the hypotensive response rate was (n = 1, 5.3%). The results show an improvement of the reports in the Clinical Hospital of Goiás compared to the reports described in the national Haemovigilance in 2014. It is less than ideal and it reflects the situation of the hemotherapy in country, with few reports and a small production of national knowledge on the subject.